Outcomes of Sacral Neuromodulation in a Privately Insured Population. Issue 7 (5th August 2016) - Anger, Jennifer T.; Cameron, Anne P.; Madison, Rodger; Saigal, Christopher; Clemens, J. Quentin; ,
Abstract : Objective: In this study, we analyzed claims data from the Ingenix data base to analyze outcomes of sacral neuromodulation with respect to both provider and patient factors. Materials and Methods: We used the Ingenix (I3) data base to determine demographic, diagnosis, and procedure success information for years 2002–2007 for privately insured patients. Demographic information was obtained, as were the diagnoses given and procedures performed, based on ICD‐9 diagnosis codes and Current Procedural Terminology procedure codes. Multivariate analysis was performed to identify specific predictors of success, as measured by progression to implantation of a pulse generator. Results: Overall success, as defined by battery placement, was 49.1%. Fifty‐one percent of staged procedures were followed by battery placement compared with 24.1% of percutaneous cases ( p < 0.0001). Among the patient variables analyzed, women were more likely than men to progress to battery placement. After Stage I testing, patients treated by urologists were overall more likely than gynecologists to proceed to battery placement (I3: 54% vs. 47%, p < 0.0001). Unlike previous findings in other claims‐based data sets, we did not observe a provider‐volume relationship in the i3 data set. Conclusions: Success of sacral neuromodulation, as defined by proceeding to battery placement, was much better after formal staged procedures, which leads us to question the utility of percutaneous techniques. Outcomes were also better among female patients and among those treated by a urologist. Specialty differences will likely diminish over time as more gynecologists adopt sacral neuromodulation.